6. Design - Synthesis Phenomenon: Art, Science and Technology - Florea Eleonora (Sciendo, 2022)
In the nineteenth century, the century of electricity and railways, radio and cinema, in the process of vertiginous technical progress, within the industrial civilization, appears a new phenomenon of creative, artistic and scientific activity - design. It gave birth to a "way of industrial thinking", oriented towards creating useful and functional objects, but at the same time able to delight the eye with their beauty without recurring to ornament and decoration effects.